Factors affecting Modern Apprenticeship completion rates in Scotland - Greig, Malcolm (International Journal of Population Data Science, 2018)
Background Completing an apprenticeship has been shown to be a critical to an individual’s future employment, earnings and career. International research, notably in England, Australia and Germany, has identified features of the apprentice, employer and training associated with completion. However there has been no comparable research in Scotland, which operates a distinct apprenticeship system. Access to longitudinal data on apprentices in Scotland provides a unique opportunity to examine this. Objectives The aim of this study was to look at potential factors associated with successful apprenticeship completion. Specifically, to identify apprentices most likely to complete, those who may require additional support, and to pinpoint good practice in training provision that could help improve completion rates. The paper considers why some apprentices are more likely to complete and discusses policy implications for Scotland and beyond. Methods Logistic regression was conducted on administrative records of apprenticeship leavers in Scotland, covering 2007 to 2015. Altogether 78,952 leavers were analysed, consisting of 59,737 completers and 19,215 non-completers. This isolated the impact of each factor on the probability of completion holding other factors constant. This is the first time that extensive administrative data has been used to model apprenticeship completions in Scotland. Findings A positive relationship with completion was found for female apprentices and those from less deprived areas, although women were less likely to complete in certain subjects. Apprentices employed by a large employer, training with public sector organisations and in selected technical frameworks were also more likely to complete. Conclusions This research suggests a number of factors that have a significant impact on the chances of completion. It identifies a need to support apprentices identified as most at risk of not completing, and to create an environment more conducive to completion in frameworks and industries where apprentices are more likely to drop out.